A comparison of exclusive breastfeeding in Belgian maternity facilities with and without Baby‐friendly Hospital status. Issue 4 (11th June 2019) - Robert, Emmanuelle; Michaud‐Létourneau, Isabelle; Dramaix‐Wilmet, Michèle; Swennen, Béatrice; Devlieger, Roland
Abstract: A retrospective cross‐sectional study was carried out in Wallonia (the southern region of Belgium) in which a 20‐question breastfeeding (BF) module was included in an immunization survey. The purpose of this paper is to compare exclusive breastfeeding (EBF) prevalences and BF practices for mothers giving birth in Baby‐friendly Hospital Initiative (BFHI) and non‐BFHI maternity facilities. A total of 557 mothers responded to BF questions when their child was 18–24 months old; 26.7% of them delivered in a BFHI maternity facility. At discharge, a larger proportion of children were exclusively breastfed if they were born in a BFHI maternity facility (76.5% vs. 65.8%, p = .02). The median duration of EBF (15.0 vs. 12.9 weeks, p = .3), and the proportion of children exclusively breastfed at 5 months (16.8% vs 15.8%, p = 1.0) were similar in both groups. Few mothers knew that EBF was recommended for the first 6 months of life (28.6% in BFHI vs 23.1% in non‐BFHI, p = .2). For most groups of the population examined, the rates of BF tended to be higher in BFHI facilities, but many differences were not significant. More specifically, BFHI seemed to boost BF practices among mothers more likely to breastfeed, but the Initiative did not seem to trigger enhanced BF practices in mothers traditionally less likely to breastfeed (except for indifferent/negative partner's attitude and mothers of Belgian origin). Influencing the BF practices of mothers less likely to breastfeed requires a special attention with complementary actions in maternity facilities as well as in community services.